Capital Flows to Transition Economies : Master or Servant? - Lipschitz, Leslie; Lane, Timothy; Mourmouras, Alex. (Washington, D.C. : International Monetary Fund, 2002)
This paper discusses the forces driving capital flows in the transition countries of Central and Eastern Europe (CEE). It argues that various influences-specifically, the real exchange rate history and trend and the factor intensity of production-can combine to motivate very large capital inflows. These inflows can either undermine attempts at monetary restraint or force excessive appreciations. They can also render the economy highly vulnerable to shifts in market sentiment. The policy implications of the analysis are awkward: exposure to global capital markets sets up difficult dilemmas for policy and leads to vulnerabilities that can be reduced but not eliminated.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet